1, 4: 3, 6-diglycidyl hexanehexol polyester / nano rubber particle blend material as well as preparation method and application of 1, 4: 3, 6-diglycidyl hexanehexol polyester / nano rubber particle blend material

By blending and modifying 1,4:3,6-di-shrinked hexanhexanol polyester with nanorubber particles, the problem of deformation and performance degradation of PET materials at high temperatures is solved, and a blended material with high impact strength, high transparency, and high heat resistance is achieved, and its application in films, fibers and packaging materials has been expanded.

CN119684755APending Publication Date: 2025-03-25INST OF CHEM CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311242259.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing PET materials will experience severe deformation and performance degradation at higher temperatures, while maintaining high transparency of the material while improving heat resistance and impact strength.

Method used

By blending and modifying 1,4:3,6-disulfinated hexanhexanol polyester with nanorubber particles, combining heat stabilizers and antioxidants, a blend material with high impact strength, high transparency and high heat resistance was prepared by melt blending.

Benefits of technology

It achieves significantly improving the impact performance of PET materials without affecting the transparency and heat resistance of polyester, and provides a high-performance engineering plastic suitable for the preparation of films, fibers and heat-resistant packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004467752590000021
    Figure BDA0004467752590000021
  • Figure BDA0004467752590000031
    Figure BDA0004467752590000031
  • Figure FDA0004467752580000011
    Figure FDA0004467752580000011
Patent Text Reader

Abstract

The invention provides a blend material with high impact strength, high transparency and high heat resistance and a preparation method thereof, and the obtained 1, 4: 3, 6-diglycidyl hexanehexol polyester / nano rubber particles are subjected to blending modification, so that the defect of poor impact property of heat-resistant 1, 4: 3, 6-diglycidyl hexanehexol polyester is overcome on the premise of not influencing the transparency and heat resistance of polyester.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a heat-resistant 1,4:3,6-hexadecene polyester / nano rubber particle blend material with high impact strength and high transparency, and a preparation method and application thereof. Background Art

[0002] Polyethylene terephthalate (PET) is one of the most widely used engineering plastics and is widely used in many fields such as fiber, film, and packaging. At present, my country's PET production capacity has reached 54 million tons / year, but PET has a low glass transition temperature. At higher temperatures, PET will suffer from serious deformation and a significant drop in performance. 1,4:3,6-hexanedipyrol is produced by enzymatic decomposition of starch in cereals into polysaccharides, which are hydrogenated to obtain hexahydric alcohols, and then further lose two molecules of water to obtain 1,4:3,6-hexanedipyrol. This bio-based raw material has three isomers, namely isosorbide, isomannide, and isoidide. Among them, only isosorbide has achieved large-scale industrial production. Isosorbide is non-toxic and has the advantages of being green and environmentally friendly. It is also a chiral molecule with a rigid structure, which can effectively improve the heat resistance and mechanical properties of polymers. Introducing isosorbide into PET can effectively improve its heat resistance, but the rigid structure of isosorbide also causes the impact strength of the copolymer to decrease. If glass fiber reinforcement is added, the impact strength can be effectively improved, but the transparency of the material will be greatly lost. Therefore, while improving the heat resistance and impact strength, maintaining the high transparency of the material is also a problem that is of great concern and needs to be solved urgently.

[0003] In summary, in view of the poor impact resistance of 1,4:3,6-hexadecene modified PET and the opacity of the material caused by doping reinforcing materials, how to prepare high heat resistance, impact resistance and high transparency materials through a simple method to improve their added value and expand their application scope is an urgent problem to be solved. Summary of the invention

[0004] The purpose of the present invention is to improve the problem of poor impact performance of heat-resistant 1,4:3,6-hexanedol polyester without affecting the transparency and heat resistance of the polyester by blending and modifying heat-resistant 1,4:3,6-hexanedol polyester / nano rubber particles, and provide a high-impact strength, high-transparency and high-heat-resistant blend material and a preparation method thereof.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] A 1,4:3,6-hexadecene polyester / nano rubber particle blend, which is obtained by melt blending copolyester 1 with nano rubber particles, a heat stabilizer and an antioxidant;

[0007] Wherein, the copolyester 1 is prepared by a polyester prepolymer 1 through a polycondensation reaction; the polyester prepolymer 1 is prepared by an esterification reaction or an ester exchange reaction of a compound represented by formula A, ethylene glycol, 1,4;3,6-dihydrohexanedol, and a diol represented by formula B;

[0008] Formula A: R 1 OOC-L-COOR 1

[0009] Formula B: HO-R-OH

[0010] R 1 The same or different, independently selected from H, unsubstituted or optionally substituted by one, two or more Ra: C 1-12 Alkyl or C 6-20 Aryl;

[0011] L is selected from C which is unsubstituted or optionally substituted with one, two or more Rb 6-20 Aryl;

[0012] R is selected from C 3-12 Alkyl, -C 1-6 Alkyl-C 3-12 Cycloalkyl-C 1-6 Alkyl- or C 3-12 Cycloalkyl;

[0013] Ra and Rb are the same or different and are independently selected from halogen, C 1-12 Alkyl, haloC 1-12 Alkyl or C 1-12 Alkoxy;

[0014] The 1,4;3,6-dihydrohexanedol is selected from at least one of isosorbide, isomannide and isoidide,

[0015]

[0016] The heat stabilizer is selected from at least one of phosphite heat stabilizers;

[0017] The antioxidant is selected from hindered phenol antioxidants.

[0018] According to an embodiment of the present invention, the compound R 1 OOC-L-COOR 1 represents dibasic acids and / or dibasic esters, for example, the compound represented by formula A represents one dibasic acid, one dibasic ester, two or more dibasic acids, two or more dibasic esters, or a mixture of one or more dibasic acids and one or more dibasic esters. Similarly, the diol HO-R-OH represented by formula B can be a mixture of one or more diols.

[0019] According to an embodiment of the present invention, R 1 Selected from H, C 1-10 Alkyl or C 6-14 Aryl, such as R 1 is selected from H, ethyl, propyl, butyl, pentyl, hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, 2-methylbutyl, 1-methylbutyl, 1-ethylpropyl, 1,2-dimethylpropyl, neopentyl, 1,1-dimethylpropyl, 4-methylpentyl, 3-methylpentyl, 2-methylpentyl, 1-methylpentyl, 2-ethylbutyl, 1-ethylbutyl, 3,3-dimethylbutyl, 2,2-dimethylbutyl, 1,1-dimethylbutyl, 2,3-dimethylbutyl, 1,3-dimethylbutyl, 1,2-dimethylbutyl, phenyl or naphthyl.

[0020] According to an embodiment of the present invention, the polyester prepolymer 1 has a structural unit shown in the following formula I:

[0021]

[0022] Wherein, L is selected from C 6-14 Aryl, for example phenyl or naphthyl.

[0023] According to the embodiment of the present invention, based on the total molar amount of the copolyester diol, the molar percentage of the 1,4;3,6-dihydrohexanedol unit in Formula I is 10-90%, the molar percentage of the ethylene glycol unit is 1-90%, and the molar percentage of other diol units is 1-90%.

[0024] According to the embodiment of the present invention, the molar percentage of the terephthalic acid unit in Formula I is 70-100% based on the total molar amount of the dibasic acid. If other acids are contained, the molar content of other dibasic acid units is 0-30%;

[0025] According to an embodiment of the present invention, calculated based on the total mass of the blend, in the 1,4:3,6-diglycol polyester / nano rubber particle blend, the mass fraction of the 1,4:3,6-diglycol polyester is 90% to 99.5%; the mass fraction of the nano rubber particles is 0.5% to 10%.

[0026] According to an embodiment of the present invention, calculated based on the total mass of the blend, the mass fraction of the 1,4:3,6-hexadecene polyester is 96% to 98%; the mass fraction of the nano rubber particles is 2% to 4%.

[0027] According to an embodiment of the present invention, the mass ratio of the copolyester 1 to the nano-rubber particles, the heat stabilizer and the antioxidant is (80-120):(0.5-10):(0.01-1):(0.01-1), for example, (90-110):(1-8):(0.05-0.5):(0.05-0.5), such as 95:5:0.1:0.2, 96:4:0.2:0.1, 97:3:0.15:0.17, 98:2:0.2:0.12 or 99:1:0.3:0.1.

[0028] According to an embodiment of the present invention, the molar ratio of the compound represented by formula A and the diol (including ethylene glycol, 1,4;3,6-diglycol and the diol represented by formula B) for preparing polyester prepolymer 1 is 1:1-3, preferably 1:1.1-2.

[0029] According to an embodiment of the present invention, the molar ratio of the raw materials ethylene glycol, 1,4;3,6-diglycol, and the diol shown in formula B for preparing the polyester prepolymer 1 is 1:(0.01-1):(0.01-3), for example, 1:(0.1-1):(0.1-1.5), such as 1:0.14:0.57, 1:0.25:0.375, 1:0.86:1.43, 1:0.313:0.438, and 1:1:1.67.

[0030] According to an embodiment of the present invention, the nano rubber particles are at least one of styrene-butadiene rubber, carboxylated styrene-butadiene rubber, nitrile rubber, carboxylated nitrile rubber, acrylate rubber, ethylene vinyl acetate rubber, silicone rubber and styrene-butadiene rubber, preferably carboxylated styrene-butadiene rubber and / or carboxylated nitrile rubber.

[0031] Furthermore, the average particle size of the nano rubber particles is 20 to 500 nm, preferably 20 to 200 nm, such as 20 to 60 nm.

[0032] According to an embodiment of the present invention, the intrinsic viscosity of the 1,4:3,6-diglycol polyester / nano rubber particle blend is 0.5-1.2 dL / g, and the glass transition temperature is 70-130°C; preferably, the intrinsic viscosity of the 1,4:3,6-diglycol polyester / nano rubber particle blend is 0.5-0.9 dL / g, and the glass transition temperature is 90-115°C.

[0033] According to an embodiment of the present invention, the impact strength of the 1,4:3,6-hexadecene polyester / nano rubber particle blend is 200-550 J / m, preferably 220-480 J / m.

[0034] According to an embodiment of the present invention, the light transmittance of the 1,4:3,6-hexadecene polyester / nano rubber particles is not less than 82%, for example, 82%-99%.

[0035] According to an embodiment of the present invention, the heat stabilizer is selected from at least one of phosphite heat stabilizers, for example, one or more of triphenyl phosphite, trimethyl phosphite, and ethyl phosphite.

[0036] According to an embodiment of the present invention, the antioxidant is selected from at least one of hindered phenol antioxidants, for example, one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester, N,N-1,6-hexylene-bis-[3,5-di-tert-butyl-4-hydroxyphenylpropionamide], and N,N-bis[β(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine.

[0037] The present invention also provides a method for preparing the 1,4:3,6-hexadecene polyester / nano rubber particle blend, comprising the following steps:

[0038] (1) Esterification / transesterification reaction: the compound represented by formula A, ethylene glycol, 1,4;3,6-dihydrohexanedol, and the diol represented by formula B are mixed and subjected to esterification reaction and / or transesterification reaction to obtain a polyester prepolymer 1;

[0039] Formula A: R 1 OOC-L-COOR 1

[0040] Formula B: HO-R-OH

[0041] Among them, R 1 , L and R have the definitions as above;

[0042] (2) melt polycondensation reaction: subjecting the polyester prepolymer 1 prepared in step (1) to a polycondensation reaction to prepare a copolyester 1;

[0043] (3) The copolyester 1 prepared in step (2), the nano rubber particles, the heat stabilizer and the antioxidant are mixed, melt blended and extruded into pellets to obtain a 1,4:3,6-dihexanediol polyester / nano rubber particle blend.

[0044] According to an embodiment of the present invention, step (1) is performed under an inert gas atmosphere, such as a nitrogen atmosphere.

[0045] According to an embodiment of the present invention, in step (1), the diol represented by formula B is selected from at least one of 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 2,2-dimethyl-1,3-propylene glycol, 1,6-hexanediol, 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol, preferably 1,3-cyclohexanedimethanol and 1,4-cyclohexanedimethanol.

[0046] According to an embodiment of the present invention, in step (1), the compound represented by formula A is selected from terephthalic acid, isophthalic acid, dimethyl terephthalate, phthalic acid, 1,4-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, diethyl terephthalate, dipropyl terephthalate, dibutyl terephthalate, dioctyl terephthalate, diphenyl terephthalate, dimethyl isophthalate, dipropyl isophthalate, dibutyl isophthalate, dioctyl isophthalate, diphenyl isophthalate, dimethyl phthalate, diethyl terephthalate, dipropyl terephthalate, dibutyl terephthalate, dioctyl terephthalate, diphenyl terephthalate, dimethyl phthalate, diethyl terephthalate, dipropyl terephthalate, dibutyl terephthalate, dioctyl terephthalate, diphenyl terephthalate, At least one of diphenyl formate, dimethyl 1,4-naphthalene dicarboxylate, diethyl 1,4-naphthalene dicarboxylate, dipropyl 1,4-naphthalene dicarboxylate, dibutyl 1,4-naphthalene dicarboxylate, dioctyl 1,4-naphthalene dicarboxylate, diphenyl 1,4-naphthalene dicarboxylate, dimethyl 2,6-naphthalene dicarboxylate, diethyl 2,6-naphthalene dicarboxylate, dipropyl 2,6-naphthalene dicarboxylate, dibutyl 2,6-naphthalene dicarboxylate, dioctyl 2,6-naphthalene dicarboxylate, and diphenyl 2,6-naphthalene dicarboxylate, preferably diethyl terephthalate or dimethyl isophthalate; for example, isophthalic acid, 1,4-naphthalene dicarboxylic acid, or a mixture of terephthalic acid and phthalic acid.

[0047] According to an embodiment of the present invention, in step (1), the molar ratio of the compound dibasic acid and / or dibasic ester represented by formula A to the diol is 1:1 to 3, preferably 1:1.1 to 2;

[0048] According to an embodiment of the present invention, the esterification reaction in step (1) adopts a high temperature and high pressure esterification reaction, the reaction temperature is 200-260°C, preferably 220-260°C; the reaction pressure is 200-400KPa, preferably 200-300KPa; the total time of the esterification reaction is 2-20 hours, preferably 3-10 hours.

[0049] According to an embodiment of the present invention, in step (1), the ester exchange reaction adopts a normal pressure ester exchange reaction, the reaction temperature is 180-270°C, preferably 200-240°C; the total time of the ester exchange reaction is 2-20 hours, preferably 3-10 hours.

[0050] According to an embodiment of the present invention, in step (1), the purity of the 1,4:3,6-hexadecene is greater than 99.0%, preferably greater than 99.5%.

[0051] According to an embodiment of the present invention, step (1) is carried out in the presence of an ester exchange catalyst 1, and the ester exchange catalyst 1 is selected from at least one of metal oxides, metal hydroxides, alkoxy metal compounds, metal phosphates, metal sulfates, metal acetylacetone complexes, metal acetates and metal halides of magnesium, zinc, manganese, aluminum, cobalt and tin. For example, the ester exchange catalyst 1 is at least one of magnesium oxide, magnesium hydroxide, magnesium stearate, magnesium sulfate, magnesium acetate, magnesium chloride hexahydrate, zinc oxide, zinc hydroxide, zinc stearate, zinc phosphate, zinc sulfate, zinc acetate, manganese oxide, manganese acetylacetonate, manganese sulfate, manganese acetate, manganese chloride, aluminum oxide, aluminum hydroxide, aluminum phosphate, aluminum sulfate, aluminum acetate, cobalt oxide, cobalt acetylacetonate, cobalt acetate, cobalt acetate tetrahydrate, dibutyltin oxide, dibutyltin dichloride, tributyltin acetate, tributyltin chloride and trimethyltin chloride.

[0052] According to an embodiment of the present invention, the reaction of step (2) is carried out in the presence of a condensation polymerization catalyst, and the condensation polymerization catalyst is at least one of an organic metal compound, an oxide or a complex of titanium, antimony, silicon, germanium or zirconium; preferably at least one of titanium dioxide, a silicon dioxide / titanium dioxide composite, a zirconium dioxide / titanium dioxide composite, tetrabutyl titanate, tetraethyl titanate, antimony trioxide, antimony glycol, antimony acetate, germanium dioxide and germanium acetate.

[0053] According to an embodiment of the present invention, in step (2), the mass of the polycondensation catalyst is 0.001 wt.% to 0.05 wt.%, preferably 0.001 wt.% to 0.04 wt.%, based on the mass of the polyester prepolymer 1.

[0054] According to an embodiment of the present invention, in step (2), the temperature of the polycondensation reaction is 200-300°C, preferably 240-280°C; the time of the polycondensation reaction is 1-48 hours, preferably 3-12 hours. The pressure of the reaction system during the polycondensation reaction is less than 200Pa, preferably less than 80Pa.

[0055] According to an embodiment of the present invention, in step (3), calculated based on the total mass of the blend, the mass fraction of the copolyester 1 is 90% to 99.5%; the mass fraction of the nano rubber particles is 0.5% to 5%; preferably, the mass fraction of the heat-resistant 1,4:3,6-hexadecene polyester is 96% to 98%; and the mass fraction of the nano rubber particles is 2% to 4%.

[0056] According to an embodiment of the present invention, in step (3), the mass fraction of the heat stabilizer is 0.01% to 3%, preferably 0.05% to 1%, calculated based on the total mass of the blend.

[0057] According to an embodiment of the present invention, in step (3), the mass fraction of the antioxidant is 0.01% to 3%, preferably 0.05% to 1%, calculated based on the total mass of the blend.

[0058] According to an embodiment of the present invention, the melt blending in step (3) is carried out on a twin-screw extruder, the temperature of the twin-screw extruder is 200-260°C, preferably 220-250°C; the rotation speed is 50-500r / min, preferably 70-200r / min.

[0059] The present invention also provides the use of the above-mentioned 1,4:3,6-hexanedol polyester / nano rubber particle blend material as engineering plastics in the preparation of films, fibers, and heat-resistant packaging materials.

[0060] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:

[0061] The invention provides a high-impact strength, high-transparency and high-heat-resistant blend material and a preparation method thereof. The obtained 1,4:3,6-hexanedol polyester / nano rubber particles are blended and modified to overcome the disadvantage of poor impact performance of the heat-resistant 1,4:3,6-hexanedol polyester without affecting the transparency and heat resistance of the polyester.

[0062] The blend obtained by the method of the present invention is a transparent colorless solid with an intrinsic viscosity of 0.5-1.2 dL / g and high impact strength, and can be directly used as a plastic. Moreover, the component content of the blend is controllable, and the performance of the blend can be effectively adjusted.

[0063] Definition and explanation of terms

[0064] The term "halogen" means fluorine, chlorine, bromine and / or iodine. Accordingly, the term "halo" refers to fluoro, chloro, bromo and / or iodo. Within the scope of this document, when an atom, residue, group or moiety is halogenated, the atom at the halogenated position may be monosubstituted, disubstituted or polysubstituted up to full substitution by halogen atoms, for example, "halo C 1-12 Alkyl" etc.

[0065] In the present application, some substituents marked with "*" represent the connection site.

[0066] The term "C 1-12 "Alkyl" is understood to mean a straight-chain or branched saturated monovalent hydrocarbon group having 1 to 12 carbon atoms. For example, "C 1-10"Alkyl" means straight chain and branched chain alkyl groups having 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 carbon atoms. 1-6 The term "alkyl" refers to straight-chain and branched alkyl groups having 1, 2, 3, 4, 5 or 6 carbon atoms. The alkyl group is, for example, methyl, ethyl, propyl, butyl, pentyl, hexyl, isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, 2-methylbutyl, 1-methylbutyl, 1-ethylpropyl, 1,2-dimethylpropyl, neopentyl, 1,1-dimethylpropyl, 4-methylpentyl, 3-methylpentyl, 2-methylpentyl, 1-methylpentyl, 2-ethylbutyl, 1-ethylbutyl, 3,3-dimethylbutyl, 2,2-dimethylbutyl, 1,1-dimethylbutyl, 2,3-dimethylbutyl, 1,3-dimethylbutyl or 1,2-dimethylbutyl, or the like or isomers thereof.

[0067] The term "C 3-12 The term “alkyl” refers to straight-chain and branched alkyl groups having 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 carbon atoms, for example, propyl, butyl, pentyl, hexyl, isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, 2-methylbutyl, 1-methylbutyl, 1-ethylpropyl, 1,2-dimethylpropyl, neopentyl, 1,1-dimethylpropyl, 4-methylpentyl, 3-methylpentyl, 2-methylpentyl, 1-methylpentyl, 2-ethylbutyl, 1-ethylbutyl, 3,3-dimethylbutyl, 2,2-dimethylbutyl, 1,1-dimethylbutyl, 2,3-dimethylbutyl, 1,3-dimethylbutyl or 1,2-dimethylbutyl, etc.

[0068] The term "C 3-12 "Cycloalkyl" is understood to mean a saturated monovalent monocyclic, bicyclic hydrocarbon ring or a bridged cycloalkane having 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 carbon atoms. 3-12 The cycloalkyl group may be a monocyclic hydrocarbon group, such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl or cyclodecyl, or a bicyclic hydrocarbon group such as decalin. The cycloalkyl group may be a spiro ring, such as spiro [3,3] ring, spiro [3,4] ring, spiro [3,5] ring, spiro [4,4] ring, spiro [4,5] ring, spiro [5,5] ring.

[0069] The term "C 6-20 "Aryl" is understood to mean preferably a monovalent aromatic or partially aromatic monocyclic, bicyclic or tricyclic hydrocarbon ring having 6 to 20 carbon atoms, preferably "C 6-14 The term "C 6-14 The term "aryl" is understood to mean preferably a monovalent aromatic or partially aromatic monocyclic, bicyclic or tricyclic hydrocarbon ring ("C 6-14or a ring having 9 carbon atoms ("C9 aryl"), for example indanyl or indenyl, or a ring having 10 carbon atoms ("C 10 aryl), such as tetrahydronaphthyl, dihydronaphthyl or naphthyl, or a ring having 13 carbon atoms ("C 13 aryl), such as fluorenyl, or a ring having 14 carbon atoms ("C 14 aryl”), such as anthracenyl. When the C 6-20 When the aryl group is substituted, it may be monosubstituted or polysubstituted. Also, there is no limitation on the substitution position, for example, it may be substituted at the ortho position, para position or meta position.

[0070] The term "halogenated C 1-12 "Alkyl" means C 1-12 In the case where the H on the alkyl group is optionally substituted by 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 halogens, the term “halo” and “C 1-12 "Alkyl" has the above definition. The substitution is on the same carbon atom or on different carbon atoms. 1-6 Alkyl". The "halogenated C 1-12 "Alkyl" is, for example, trifluoromethyl.

[0071] The term "C 1-12 "Alkoxy" means C 1-12 In the case where 1, 2 or 3 carbon atoms in the alkyl group are replaced by O, the above and "C 1-12 "Alkyl" has the above definition. Optionally "C 1-6 Alkoxy". The "C 1-12 "Alkoxy" is, for example, methoxy, ethoxy or propoxy. DETAILED DESCRIPTION

[0072] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.

[0073] The performance parameters in the following examples are measured according to the following methods.

[0074] Intrinsic viscosity: 0.125 g of the copolyester was dissolved in 25 mL of phenol tetrachloroethane solution, and the intrinsic viscosity of the polymer was measured using an Ubbelohde viscometer in a thermostat at 25°C.

[0075] Glass transition temperature: The copolyester was heated at a constant temperature of 300°C for 5 minutes. After the thermal history was eliminated, the temperature in the furnace was rapidly cooled to room temperature. The glass transition temperature of the copolyester was measured during the second scan at a heating rate of 10°C / min.

[0076] Impact strength: The Izod impact strength of a copolyester sample with a notch prepared with a thickness of 4 mm was measured at 23° C. using an Izod impact strength tester according to GB-T1843-2008.

[0077] Light transmittance: Use a light transmittance meter to measure the light transmittance of a 50 mm round copolyester sample at 23°C according to GB / T2410-2008.

[0078] Example 1. Preparation of heat-resistant 1,4:3,6-hexadecene polyester / nano rubber particle blend

[0079] (1) In a 500 mL glass flask, 66.4 g (0.4 mol) of terephthalic acid, 16.6 g (0.1 mol) of phthalic acid, 21.7 g (0.35 mol) of ethylene glycol, 7.3 g (0.05 mol) of isosorbide, and 28.8 g (0.2 mol) of 1,3-cyclohexanedimethanol (the molar ratio of dibasic acid to diol is 1:1.2) are added under a nitrogen atmosphere. The system temperature is gradually increased to 247°C under a pressure of 310 kPa, and the reaction is carried out for 4 hours. The by-product water produced by the reaction is completely evaporated to obtain a copolyester prepolymer I-1. 196 g of prepolymer I-1 is added to a 500 mL glass flask, 0.02 wt% of antimony acetate as a polycondensation catalyst is added, and a vacuum is gradually established to 80 Pa. The reaction is carried out at 273°C for 4.2 hours to obtain a copolyester.

[0080] (2) 95g of copolyester, 5g of nano carboxylated styrene butadiene rubber particles (particle size 20nm), 0.1g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 0.2g of trimethyl phosphite were mixed uniformly, and the uniformly mixed blend was added to a twin-screw extruder, the extruder temperature was set to 240°C, the speed was set to 70r / min, and the blend was extruded and granulated to obtain a heat-resistant 1,4:3,6-dihexane hexyl polyester / nano rubber particle blend. The blend was characterized, and its intrinsic viscosity was 0.68g / dL, the glass transition temperature was 88°C, the impact strength was 343J / m, and the transmittance was 86%.

[0081] Example 2. Preparation of heat-resistant 1,4:3,6-hexadecene polyester / nano rubber particle blend

[0082] (1) In a 500 mL glass flask, 83.0 g (0.5 mol) of terephthalic acid, 24.8 g (0.4 mol) of ethylene glycol, 14.6 g (0.1 mol) of isosorbide, and 21.6 g (0.15 mol) of 1,4-cyclohexanedimethanol (the molar ratio of dibasic acid to diol is 1:1.3) are added under a nitrogen atmosphere. Under a pressure of 280 kPa, the system temperature is gradually increased to 245°C, and the reaction is carried out for 3.5 hours. The by-product water produced by the reaction is completely evaporated to obtain a copolyester prepolymer I-2. 99 g of prepolymer I-2 is added to a 250 mL glass flask, and 0.013 wt% of a polycondensation catalyst tetrabutyl titanate is added. The vacuum is gradually established to 100 Pa, and the reaction is carried out at 280°C for 4 hours to obtain a copolyester.

[0083] (2) 96g of copolyester, 4g of nano carboxyl nitrile rubber particles (particle size 30nm), 0.2g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 0.1g of triphenyl phosphite were mixed uniformly, and the uniformly mixed blend was added to a twin-screw extruder. The extruder temperature was set to 255°C and the speed was 100r / min. The blend was extruded and granulated to obtain a heat-resistant 1,4:3,6-dihexane hexyl polyester / nano rubber particle blend. The blend was characterized, and its intrinsic viscosity was 0.65g / dL, the glass transition temperature was 100°C, the impact strength was 306J / m, and the transmittance was 88%.

[0084] Example 3. Preparation of heat-resistant 1,4:3,6-hexadecene polyester / nano rubber particle blend

[0085] (1) In a 500 mL glass flask, 97.0 g (0.5 mol) of dimethyl terephthalate, 10.66 g (0.175 mol) of ethylene glycol, 18.25 g (0.125 mol) of isosorbide, 36.0 g (0.25 mol) of 1,4-cyclohexanedimethanol (the molar ratio of dibasic acid ester to diol is 1:1.1) and 0.022 wt% of ester exchange catalyst zinc acetate were added under nitrogen atmosphere. Under a pressure of 290 kPa, the system temperature was gradually increased to 252°C, and the reaction was carried out for 4.5 hours. The by-product methanol produced by the reaction was completely evaporated to obtain a copolyester prepolymer I-3. 199 g of prepolymer I-3 was added to a 250 mL glass flask, 0.036 wt% of polycondensation catalyst antimony trioxide was added, and a vacuum was gradually established to 90 Pa. The reaction was carried out at 275°C for 4.9 hours to obtain a copolyester.

[0086] (2) 97g of copolyester, 3g of nano carboxylated styrene butadiene rubber particles (particle size 25nm), 0.15g of N,N-1,6-hexylene-di-[3,5-di-tert-butyl-4-hydroxyphenylpropionamide], and 0.17g of triphenyl phosphite were mixed uniformly, and the uniformly mixed blend was added to a twin-screw extruder. The extruder temperature was set to 245°C and the speed was 85r / min. The blend was extruded and granulated to obtain a heat-resistant 1,4:3,6-dihydrohexanedol polyester / nano rubber particle blend. The blend was characterized, and its intrinsic viscosity was 0.71g / dL, the glass transition temperature was 116°C, the impact strength was 271J / m, and the transmittance was 89%.

[0087] Example 4. Preparation of heat-resistant 1,4:3,6-hexadecene polyester / nano rubber particle blend

[0088] (1) In a 1000 mL glass flask, 166.0 g (1.0 mol) of terephthalic acid, 49.6 g (0.8 mol) of ethylene glycol, 36.5 g (0.25 mol) of isosorbide, and 50.4 g (0.35 mol) of 1,4-cyclohexanedimethanol (the molar ratio of dibasic acid to diol is 1:1.4) are added under a nitrogen atmosphere. The system temperature is gradually increased to 250° C. at a pressure of 320 kPa, and the reaction is carried out for 4 hours. The by-product water produced by the reaction is completely evaporated to obtain a copolyester prepolymer I-4. 96 g of the prepolymer I-4 is added to a 250 mL glass flask, and 0.013 wt.% of a polycondensation catalyst germanium dioxide is added. The vacuum is gradually established to 80 Pa, and the reaction is carried out at 280° C. for 5 hours to obtain a copolyester.

[0089] (2) 98g of copolyester, 2g of nano acrylic rubber particles (particle size 50nm), 0.2g of N,N-1,6-hexylene-di-[3,5-di-tert-butyl-4-hydroxyphenylpropionamide], and 0.12g of triethyl phosphite were mixed uniformly, and the uniformly mixed blend was added to a twin-screw extruder. The extruder temperature was set to 245°C and the speed was 97r / min. The blend was extruded and granulated to obtain a heat-resistant 1,4:3,6-dihexyl polyester / nano rubber particle blend. The blend was characterized and its intrinsic viscosity was 0.75g / dL, the glass transition temperature was 112°C, the impact strength was 263J / m, and the transmittance was 91%.

[0090] Example 5. Preparation of heat-resistant 1,4:3,6-hexadecene polyester / nano rubber particle blend

[0091] (1) In a 1000 mL glass flask, 166.0 g (1 mol) of terephthalic acid, 18.6 g (0.3 mol) of ethylene glycol, 43.8 g (0.3 mol) of isosorbide, and 72.0 g (0.5 mol) of 1,3-cyclohexanedimethanol (the molar ratio of dibasic acid to diol is 1:1.1) are added under a nitrogen atmosphere. The system temperature is gradually increased to 255°C under a pressure of 330 kPa, and the reaction is carried out for 3.5 hours. The by-product water produced by the reaction is completely evaporated to obtain a copolyester prepolymer I-5. 100 g of the prepolymer I-5 is added to a 250 mL glass flask, and 0.025 wt% of a polycondensation catalyst silica / titanium dioxide composite is added. The vacuum is gradually established to 110 Pa, and the reaction is carried out at 280°C for 4.8 hours to obtain a copolyester.

[0092] (2) 99g of copolyester, 1g of nano carboxylated styrene butadiene rubber particles (particle size 35nm), 0.3g of N,N-1,6-hexylene-di-[3,5-di-tert-butyl-4-hydroxyphenylpropionamide], and 0.1g of triphenyl phosphite were mixed uniformly, and the uniformly mixed blend was added to a twin-screw extruder. The extruder temperature was set to 237°C and the speed was 105r / min. The blend was extruded and granulated to obtain a heat-resistant 1,4:3,6-dihexyl polyester / nano rubber particle blend. The blend was characterized, and its intrinsic viscosity was 0.69g / dL, the glass transition temperature was 125°C, the impact strength was 221J / m, and the transmittance was 92%.

[0093] Comparative Example 1

[0094] (1) In a 5L reactor, 1660 g (10 mol) of terephthalic acid, 589 g (9.5 mol) of ethylene glycol, and 365 g (2.5 mol) of isosorbide (the molar ratio of dibasic acid to diol is 1:1.2) were added under a nitrogen atmosphere. Under a pressure of 280 kPa, the system temperature was gradually increased to 252°C and reacted for 3.7 hours. The by-product water produced by the reaction was completely evaporated to obtain a copolyester prepolymer.

[0095] (2) 2000 g of prepolymer and 0.012 wt.% of polycondensation catalyst tetrabutyl titanate were added to a 5 L reactor, vacuum was gradually established to 90 Pa, and the reaction was carried out at 276° C. for 4.2 hours to obtain a copolyester. The copolyester was characterized and its intrinsic viscosity was 0.69 g / dL, glass transition temperature was 111° C., impact strength was 15 J / m, and light transmittance was 91%.

[0096] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A 1,4:3,6-hexanedipyrol polyester / nano rubber particle blend, characterized in that: It is obtained by melt blending copolyester 1 with nano rubber particles, heat stabilizer and antioxidant; Wherein, the copolyester 1 is prepared by a polyester prepolymer 1 through a polycondensation reaction; the polyester prepolymer 1 is prepared by an esterification reaction or an ester exchange reaction of a compound represented by formula A, ethylene glycol, 1,4;3,6-dihydrohexanedol, and a diol represented by formula B; Formula A: R 1 OOC-L-COOR 1 Formula B: HO-R-OH R 1 The same or different, independently selected from H, unsubstituted or optionally substituted by one, two or more Ra: C 1-12 Alkyl or C 6-20 Aryl; L is selected from C which is unsubstituted or optionally substituted with one, two or more Rb 6-20 Aryl; R is selected from C 3-12 Alkyl, -C 1-6 Alkyl-C 3-12 Cycloalkyl-C 1-6 Alkyl- or C 3-12 Cycloalkyl; Ra and Rb are the same or different and are independently selected from halogen, C 1-12 Alkyl, haloC 1-12 Alkyl or C 1-12 Alkoxy; The 1,4;3,6-dihydrohexanedol is selected from at least one of isosorbide, isomannide and isoidide, The heat stabilizer is selected from at least one of phosphite heat stabilizers; The antioxidant is selected from hindered phenol antioxidants.

2. The 1,4:3,6-hexadecene polyester / nano rubber particle blend according to claim 1, characterized in that: R 1 Selected from H, C 1-10 Alkyl or C 6-14 Aryl, such as R 1 is selected from H, ethyl, propyl, butyl, pentyl, hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, 2-methylbutyl, 1-methylbutyl, 1-ethylpropyl, 1,2-dimethylpropyl, neopentyl, 1,1-dimethylpropyl, 4-methylpentyl, 3-methylpentyl, 2-methylpentyl, 1-methylpentyl, 2-ethylbutyl, 1-ethylbutyl, 3,3-dimethylbutyl, 2,2-dimethylbutyl, 1,1-dimethylbutyl, 2,3-dimethylbutyl, 1,3-dimethylbutyl, 1,2-dimethylbutyl, phenyl or naphthyl.

3. The 1,4:3,6-hexadecene polyester / nano rubber particle blend according to claim 1 or 2, characterized in that: The polyester prepolymer 1 has a structural unit shown in the following formula I: Wherein, L is selected from C 6-14 Aryl.

4. The 1,4:3,6-hexadecene polyester / nano rubber particle blend according to any one of claims 1 to 3, characterized in that: Calculated based on the total molar amount of the copolyester diol, the molar percentage of the 1,4;3,6-dihydrohexanedol unit in formula I is 10-90%, the molar percentage of the ethylene glycol unit is 1-90%, and the molar percentage of other diol units is 1-90%. Preferably, the molar percentage of the terephthalic acid unit in Formula I is 70-100% based on the total molar amount of the dibasic acid. If other acids are contained, the molar content of other dibasic acid units is 0-30%; Preferably, calculated based on the total mass of the blend, in the 1,4:3,6-hexanedipyrin polyester / nano rubber particle blend, the mass fraction of the 1,4:3,6-hexanedipyrin polyester is 90% to 99.5%; the mass fraction of the nano rubber particles is 0.5% to 10%. Preferably, the mass ratio of the copolyester 1 to the nano rubber particles, the heat stabilizer and the antioxidant is (80-120):(0.5-10):(0.01-1):(0.01-1). Preferably, the molar ratio of the compound represented by the raw material formula A to the diol (including ethylene glycol, 1,4;3,6-dihydrohexanedol and the diol represented by the formula B) for preparing the polyester prepolymer 1 is 1:1-3. Preferably, the molar ratio of the raw materials ethylene glycol, 1,4;3,6-dihydrohexanedol, and the diol represented by formula B for preparing the polyester prepolymer 1 is 1:(0.01-1):(0.01-3).

5. The 1,4:3,6-hexadecene polyester / nano rubber particle blend according to any one of claims 1 to 4, characterized in that: The nano rubber particles are at least one of styrene butadiene rubber, carboxylated styrene butadiene rubber, nitrile rubber, carboxylated nitrile rubber, acrylic rubber, ethylene vinyl acetate rubber, silicone rubber and styrene butadiene rubber cross-linked by radiation. Preferably, the intrinsic viscosity of the 1,4:3,6-hexanedipyrol polyester / nano rubber particle blend is 0.5-1.2 dL / g, and the glass transition temperature is 70-130°C.

6. The 1,4:3,6-hexadecene polyester / nano rubber particle blend according to any one of claims 1 to 5, characterized in that: The heat stabilizer is selected from one or more of triphenyl phosphite, trimethyl phosphite and ethyl phosphite. Preferably, the antioxidant is selected from one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester, N,N-1,6-hexylene-bis-[3,5-di-tert-butyl-4-hydroxyphenylpropionamide], and N,N-bis[β(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine.

7. The method for preparing the 1,4:3,6-hexadecene polyester / nano rubber particle blend according to any one of claims 1 to 6, characterized in that: The steps include: (1) Esterification / transesterification reaction: the compound represented by formula A, ethylene glycol, 1,4;3,6-dihydrohexanedol, and the diol represented by formula B are mixed and subjected to esterification reaction and / or transesterification reaction to obtain a polyester prepolymer 1; Formula A: R 1 OOC-L-COOR 1 Formula B: HO-R-OH Among them, R 1 , L and R have the definitions in claim 1 or 2; (2) melt polycondensation reaction: subjecting the polyester prepolymer 1 prepared in step (1) to a polycondensation reaction to prepare a copolyester 1; (3) The copolyester 1 prepared in step (2), the nano rubber particles, the heat stabilizer and the antioxidant are mixed, melt blended and extruded into pellets to obtain a 1,4:3,6-dihexanediol polyester / nano rubber particle blend.

8. The preparation method according to claim 7, characterized in that: Step (1) is carried out in the presence of an ester exchange catalyst 1, wherein the ester exchange catalyst 1 is selected from at least one of metal oxides, metal hydroxides, alkoxy metal compounds, metal phosphates, metal sulfates, metal acetylacetonate complexes, metal acetates and metal halides of magnesium, zinc, manganese, aluminum, cobalt and tin. For example, the ester exchange catalyst 1 is at least one of magnesium oxide, magnesium hydroxide, magnesium stearate, magnesium sulfate, magnesium acetate, magnesium chloride hexahydrate, zinc oxide, zinc hydroxide, zinc stearate, zinc phosphate, zinc sulfate, zinc acetate, manganese oxide, manganese acetylacetonate, manganese sulfate, manganese acetate, manganese chloride, aluminum oxide, aluminum hydroxide, aluminum phosphate, aluminum sulfate, aluminum acetate, cobalt oxide, cobalt acetylacetonate, cobalt acetate, cobalt acetate tetrahydrate, dibutyltin oxide, dibutyltin dichloride, tributyltin acetate, tributyltin chloride and trimethyltin chloride. Preferably, the reaction of step (2) is carried out in the presence of a condensation polymerization catalyst, wherein the condensation polymerization catalyst is at least one of an organic metal compound, an oxide or a complex of titanium, antimony, silicon, germanium or zirconium; preferably at least one of titanium dioxide, a silicon dioxide / titanium dioxide composite, a zirconium dioxide / titanium dioxide composite, tetrabutyl titanate, tetraethyl titanate, antimony trioxide, antimony glycol, antimony acetate, germanium dioxide and germanium acetate.

9. The preparation method according to claim 8, characterized in that: The melt blending in step (3) is carried out on a twin-screw extruder, the temperature of the twin-screw extruder is 200-260° C., and the rotation speed is 50-500 r / min.

10. Use of the 1,4:3,6-hexanedipyrol polyester / nano rubber particle blend material as claimed in any one of claims 1 to 6 as engineering plastics in the preparation of films, fibers and heat-resistant packaging materials.